DIMENSI KONDISIONALITAS DAN FLEKSIBILITAS AL-QUR'AN BAGI IMPLEMENTASI FATWA DSN-MUI TENTANG PRODUK BANK SYARIAH - Ahmad Hasan Ridwan; Asep Rahmat (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: This study discusses the dimensions of the conditionality of the Koran, the flexibility of the Koran, and the implementation of the National Sharia Council of the Indonesian Ulema Council Center for the dimension of conditionality and the dimension of the flexibility of the Koran regarding sharia bank products in Indonesia. With a qualitative approach and content analysis method, it is found that the conditionality of the Koran means the conditioning demanded by ‘illat al-hukm (legal motives) within the framework of tathbiq al-hukm (application of the law). The dimension of the versatility of the Koran shows that the existence of the Koran is always flexible in responding to demands the size of the place and time that surrounds it without ignoring the objectives of the shari'a. Indonesia has an Indonesian Ulama Council (MUI) which appoints its National Sharia Council (DSN) -MUI work unit as a fatwa authority institution that enters into the sharia application legislation regulation legislation practiced by the banking world in Indonesia. Islamic banks after obtaining legislation from Bank Indonesia and issued regulations by the Financial Services Authority (OJK). The presence of the DSN Fatwa institution is evidence of the dimensions of conditionality and flexibility of the verses of the Koran in the field of Islamic economics.Abstrak: Penelitian ini membahas tentang dimensi kondisionalitas Al-Qur’an, fleksibilitas Al-Qur’an, dan implementasi Dewan Syariah Nasional Majelis Ulama Indnonesia Pusat dimensi kondisionalitas dan dimensi fleksibilitas Al-Qur’an tentang produk bank syari’ah di Indonesia. Dengan pendekatan kualitatif dan metode analisis isi (content analysis) diperoleh bahwa kondisionalitas Al-Qur’an bermakna pengkondisian yang dituntut oleh ‘illat al-hukm (motif hukum) dalam kerangka tathbiq al-hukm (pengaplikasian hukum). Dimensi fleksibilitas Al-Qur’an menunjukkan bahwa eksistensi Al-Qur’an senantiasa luwes merespon tuntutan, seukuran dengan tempat dan waktu yang melingkupinya tanpa mengabaikan tujuan syari’ah. Indonesia memiliki lembaga Majelis Ulama Indonesia (MUI) yang menunjuk unit kerjanya Dewan Syariah Nasioanl (DSN) MUI sebagai lembaga otoritas fatwa yang masuk ke dalam wilayah regulasi legislasi aplikasi akad syariah yang dipraktikkan oleh dunia perbankan di Indonesia. Bank syariah setelah mendapatkan legislasi dari Bank Indonesia dan diterbitkan peraturan oleh Otoritas jasa Keuangan (OJK). Kehadiran institusi Fatwa DSN merupakan bukti implikasi dimensi kondisionalitas dan fleksibilitas ayat-ayat Al-Qur’an dalam bidang ekonomi syariah.